A Case for Eustress in Grazing Animals - Villalba, Juan J.; Manteca, Xavier (Frontiers in Veterinary Science, 2019)
Herbivores grazing in extensive systems are exposed to a series of challenges, rooted in the inherent spatial and temporal variability of their environment that potentially constrain their health, nutrition, and welfare. Nevertheless, in this review, we argue that challenges induced by some biotic (e.g., vegetation) and abiotic (e.g., terrain) factors may also be viewed as “positive” sources of stress or eustress, since they present complex problems, that when solved successfully elicit a greater degree of behavioral plasticity and adaptability in grazing animals. Chemically and structurally diverse landscapes require animals to display complex behaviors and exhibit adaptive capabilities, like building a balanced and safe diet or finding shelter, which ultimately lead to positive emotional states. Thus, maintaining or enhancing the diversity occurring in natural systems represent a management approach that can be used to improve welfare and prepare the animal for an efficient adaptation to future, and potentially unknown, environmental challenges.